2006
DOI: 10.2341/05-131
|View full text |Cite
|
Sign up to set email alerts
|

Bond Strengths of a 1-Step Self-etching System to Caries-affected and Normal Dentin

Abstract: ©Operative Dentistry, 2006, 31-6, 677-681 PNR Pereira • MF Nunes PA Miguez • EJ Swift Jr Clinical RelevanceThe 1-step self-etching adhesive had significantly higher mean bond strength to normal dentin than to caries-affected dentin. Although Single Bond had a similar tendency, bonds to normal dentin and caries-affected dentin were not significantly different. SUMMARYThis study was designed to evaluate the bond strengths of a 1-step self-etching system and a 2-step "etch and rinse" adhesive system to cariesa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 10 publications
4
38
0
5
Order By: Relevance
“…It is not known which are the effects of elements from amalgam in dentin in relation to adhesive restorative procedures. As several authors have shown that caries affected dentin renders lower bond strengths to adhesive restorations, [3][4][5][6][7] caution should be exercised in applying adhesive techniques on darkened dentin after amalgam removal. Indeed…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It is not known which are the effects of elements from amalgam in dentin in relation to adhesive restorative procedures. As several authors have shown that caries affected dentin renders lower bond strengths to adhesive restorations, [3][4][5][6][7] caution should be exercised in applying adhesive techniques on darkened dentin after amalgam removal. Indeed…”
Section: Discussionmentioning
confidence: 99%
“…ZnSn(OH) 6 appeared after a few days, whilst CuSn(OH) 6 appeared later, probably due to the initial high dissolution rate of Zn compared to Cu. The small amounts of Zn in the zinc-containing amalgams play a sacrificing role in corrosion processes in dental amalgam, thereby protecting the γ 2 phase as well as the η' phase from early attack.…”
Section: Corrosion Products Of Dental Amalgammentioning
confidence: 99%
See 3 more Smart Citations